The Relationship Between Hardiness and Career Adaptability Among Twelfth-Grade Vocational High School Students in Banda Raya District, Banda Aceh - Nurzakiah, Nurzakiah; Safrilsyah, Safrilsyah; Nova, Vera (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Hardiness among twelfth-grade vocational high school students can help them face and anticipate challenges related to career adaptability. When students lack hardiness in developing the willingness to engage in career development tasks, their level of career adaptability tends to be low, which may significantly affect their future. The purpose of this study was to examine the relationship between hardiness and career adaptability among twelfth-grade students of Vocational High Schools in Banda Raya District, Banda Aceh. This study employed a quantitative approach using a correlational method. The instruments used were the Hardiness Scale, developed based on aspects adapted from the scale by Lutfi, Jasmadi, and Nova, and the Career Adaptability Scale by Savickas. The population consisted of 782 students, with a sample of 243 students selected through probability sampling using the cluster (area) sampling technique. The results of data analysis showed a correlation coefficient (r) = 0.886 with a significance value (p) = 0.000, indicating a highly significant positive relationship between hardiness and career adaptability among the students. This means that the higher the level of hardiness, the higher the level of career adaptability; conversely, the lower the hardiness, the lower the career adaptability among twelfth-grade vocational students in Banda Raya District, Banda Aceh